Analisis Pengaruh Desain dan Fungsionalitas Website terhadap Kepuasan Pengguna Streetwear X Indonesia Menggunakan Pendekatan Model UTAUT2 - Chairilica Renata Putri; Chelsea Dinda Azzahra; Gandini Kemala Rahmawati; Irmawati Carolina; Eko Yulianto (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the impact of website design and functionality on user satisfaction of Streetwear X Indonesia, using the Unified Theory of Acceptance and Use of Technology 2 (UTAUT2) model. The background of this research is based on the importance of interface quality and user experience in enhancing satisfaction and the continued use of e-commerce websites, especially in the competitive streetwear industry. The independent variables analyzed include website design, which encompasses aesthetics, navigation, and visual consistency, as well as website functionality, which includes access speed, transaction ease, and interactivity. User satisfaction is the dependent variable, serving as the key indicator of the website's acceptance and user loyalty. This research employs a quantitative approach, with Partial Least Square Structural Equation Modeling (PLS-SEM) used to test the relationships between the variables and measure the impact of each factor on user satisfaction. Data was collected through questionnaires distributed to active users of the X Indonesia website, representing various user demographics. The analysis results show that both website design and functionality have a significant positive impact on user satisfaction, emphasizing the importance of both visual appeal and operational efficiency in shaping user experience. The findings offer practical implications for website managers, suggesting that focusing on developing an attractive interface, intuitive navigation, and responsive functionality can improve user experience. Therefore, optimizing design and functionality elements strategically can increase user loyalty, enhance their interaction experience, and promote the long-term sustainability of the X Indonesia website.